2009
DOI: 10.1371/journal.pone.0007198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Working Memory Load on fMRI Resting State Pattern in Subsequent Resting Phases

Abstract: BackgroundThe default-mode network (DMN) is a functional network with increasing relevance for psychiatric research, characterized by increased activation at rest and decreased activation during task performance. The degree of DMN deactivation during a cognitively demanding task depends on its difficulty. However, the relation of hemodynamic responses in the resting phase after a preceding cognitive challenge remains relatively unexplored. We test the hypothesis that the degree of activation of the DMN followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 52 publications
17
83
0
Order By: Relevance
“…Greater activation of the left superior and middle frontal gyri and bilateral PCC during criticism more than during neutral comments across all participants, may be explained by the role of the superior and middle temporal gyri in negative emotion regulation (Ochsner and Gross 2005;Mak et al 2009), and the PCC in cognitive control of aversive stimuli (Koenigsberg et al 2010), self-evaluation of past performance (Pyka et al 2009). PCC activity is often observed in the default-mode network for working memory (Fransson and Marrelec 2008;Pyka et al 2009), as well as self-referential processing (Kumari et al 2010;Sajonz et al 2010).…”
Section: Increased Activation Of Left Superior and Middle Frontal Gyrmentioning
confidence: 96%
See 2 more Smart Citations
“…Greater activation of the left superior and middle frontal gyri and bilateral PCC during criticism more than during neutral comments across all participants, may be explained by the role of the superior and middle temporal gyri in negative emotion regulation (Ochsner and Gross 2005;Mak et al 2009), and the PCC in cognitive control of aversive stimuli (Koenigsberg et al 2010), self-evaluation of past performance (Pyka et al 2009). PCC activity is often observed in the default-mode network for working memory (Fransson and Marrelec 2008;Pyka et al 2009), as well as self-referential processing (Kumari et al 2010;Sajonz et al 2010).…”
Section: Increased Activation Of Left Superior and Middle Frontal Gyrmentioning
confidence: 96%
“…Similarly, the rostral anterior cingulate cortex (ACC) is involved in appraisal of emotional information (Ochsner and Gross 2005;Kalisch et al 2006;Polli et al 2008), specifi cally negatively valenced material (Kalisch et al 2006;Mak et al 2009), as well as confl ict detection during tasks such as emotional Stroop interference (Mohanty et al 2007). The posterior cingulate cortex (PCC) is involved in cognitive control of aversive stimuli (Koenigsberg et al 2010) and self-evaluation (Pyka et al 2009;Sajonz et al 2010). In contrast, response to positively valenced material may engage dopaminergic reward areas, such as the striatum.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies it has been shown that the more difficult the task, the greater the negative BOLD response in DMN [27,28,29]. Task difficulty can be modulated parametrically by e.g.…”
Section: Introductionmentioning
confidence: 98%
“…One way to ensure this is to adopt an experimental set-up that enables us to compare the VLF EEG under different levels of stimulation, whilst keeping everything else constant (same participants and same analysis methods). Other paradigms such as working memory tasks which manipulate memory load (Pyka et al, 2009), and simple choice reaction time attention tasks (Helps et al, :2010 could also be implemented and the oscillations contrasted with the same methodology. It would be interesting to include experimental tasks with more frequent sampling (i.e.…”
Section: The Multistage Systemmentioning
confidence: 99%